Identifying support needs of Maori students enrolled extramurally at Massey University - Barbara Brookfield; Louise MacFarlane (Journal of Open, Flexible and Distance Learning, 2012)
The purpose of this preliminary research project is to develop an overview of the difficulties which extramural Maori students in Hawkes Bay and Poverty Bay encounter. This information will be useful in deciding on the allocation of resources for meeting student support needs in the future.